Is there any place for Adult Education in the era of Lifelong Learning? - Karalis, Thanassis (Adult Education Critical Issues, 2026)
Since several years, we are in an era where the lifelong learning approach has colonized almost all areas of education. Indeed, we are moving from a view of education characterized by isolated units of organized learning to a different view of learning and education that is mainly defined in terms of the continuum of both the learning phenomena and the educational institutions. In this paper, we argue that this is a paradigm shift from an old paradigm to acquire a new form and content. and in many cases old elements are replaced by new elements. After attempting to substantiate the above-mentioned paradigm shift, we would examine these new elements. The methodological approach will be that of diachronic analysis of policy papers and data concerning key issues of adult education and lifelong learning. The following questions will be addressed: What do these transitions mean for societies and the learning citizen? Is education, including Adult Education, still considered an obligation of the state or is the citizen now obliged to attend programs for reskilling and upskilling? To what extent is the citizen held responsible for the possible mismatches between his or her qualifications and the content of labor demand?